Factors Determine the Success of Learning Reading English Texts - Rachmijati, Tri (Universitas Pendidikan Ganesha, 2024)
The ability of reading English texts is an essential in English mastery, especially in the context of formal and professional education. However, the success of reading texts is often influenced by various factors. This research aims to explore various factors that influence the effectiveness of learning to read English texts. The factors that were analysed are (1) teacher activities; (2) school facilities and services; (3) student activities; and (4) the learning process. The research was conducted using a quantitative survey approach with 279 students in 11th grade. The subjects of this research are 11th grade students with a sample size of 279 students. The analysis results show that teacher activity in the learning process does not affect learning effectiveness (tcount = 0.314 < ttable; pvalue > 0.05), as well as the availability of school facilities and services (tcount = -0.652 < ttable; pvalue > 0.05). Meanwhile, the positive influence on learning effectiveness is shown by student activity (tcount = 3.441 > ttable; pvalue < 0.05) and learning process (tcount = 2.080 > ttable; pvalue < 0.05). Overall, these four factors contribute 24.9% to the success of English text reading learning at the school. The results of this study provide important implications for the development of more effective learning strategies by considering the quality of educational facilities and the active role of teachers in the learning process, which can ultimately enhance the effectiveness of learning in reading English texts.